Inovasi dalam Pengelolaan Stock : Menerapkan Metode FIFO Melalui Prototype Sistem Informasi - Hudin, Jamal Maulana; Riyanto, Andi (INTERNAL (Information System Journal), 2024)
This research focuses on stock management at Rumah Qta Mebeul, a company specialising in the sale of household supplies. The main aims and objectives of this research are to understand how the FIFO method can be practically applied and provide benefits to the company and to improve efficiency and effectiveness of stock management through the application of the First In First Out (FIFO) method using a prototype model on the stock management information system. The FIFO method was chosen because of its ability to optimise the use of raw materials and reduce losses due to expired stock. The system development model uses a prototype model that describes the operation of the FIFO method. This approach will make it possible to better visualise how the FIFO method functions in stock management. The main findings of this research include efficiency in stock management, better control, and more accurate documentation. The results of the study show that the prototype model is able to improve the information system for stock management of goods at Rumah Qta Mebeul with the FIFO method is an effective solution to optimize stock management and reduce company losses due to unused stock.